Improving English Language Skills in Early Childhood at SPS Mawar Kebonagung Through English Day Activities - Karunia, Putri Endah; Rosidah, Ilmiyatur; Vebruary, Restiti Dewi; Oktafisari, Anggitya; Vedianty, Adinda Syalsabilla Aidha (Jurnal Inovasi dan Pengembangan Hasil Pengabdian Masyarakat, 2023)
In the eyes of society, universities are considered only to teach theory without any form of application when viewed from the perspective of social life. This can be seen from the surrounding conditions where not many university graduates can apply this theory in the field. This activity aims to bridge learning at SPS Mawar, Kebonagung Subdistrict, Pasuruan City, with a service learning approach in the English Day program to provide training for SPS Mawar Kebonagung Early Age Children (AUD) in improving their English language skills by introducing several new vocabulary through singing and fun game. This activity involved a lecturer, four PGRI Wiranegara University students, AUD SPS Mawar students, and teachers. A participatory approach is also used in this service activity to attract students' attention and make it easier for students to remember new vocabulary. Students are directly involved in the learning process. The success of providing English language teaching can increase AUD's ability or vocabulary in English by providing new inspiration in teaching children English skills with fun learning.